MOTIVATION FACTORS FOR PURSUING A PHD IN MALAYSIA: A CASE STUDY OF CHINESE INTERNATIONAL DOCTORAL STUDENTS - Lin , Yan; Nasir, Nazatul Syima Mohd (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
In light of the growing higher education across borders as a trend, the student mobility across borders internationally have received much attention. But most of the literature has concentrated on undergraduate and masters students in well-established Anglophone destinations and the doctoral level mobility to new Global South destinations is yet to be explored. To fill this gap, the research explores the incentives behind Chinese students studying doctoral programs in Malaysia via a qualitative case study that was undertaken in a public university in Malaysia. The semi-structured interview with six Chinese doctoral students was used to produce data that were analyzed via thematic analysis. According to the findings, the decision making of participants was impacted on the basis of staged decision making. In the structural context, fierce competition to be admitted into the doctoral program in China and pressures associated with the advancement of careers were the most significant push factors, whereas Malaysia had a relatively easy admissions process, relative geographical proximity, affordability as well as a flexible doctoral structure which served as major pull factors. On an individual level, those external circumstances were filtered through the lens of expectancy-value appraisals such as the perception of possible success, professional and academic value, and the expected cost of study abroad in terms of money, time and emotions. The results also indicate a repetitive conflict of prestige and accessibility whereby Malaysia has frequently been chosen as a viable and desirable middle-ground destination. Combining the Push-Pull theory and the Expectancy-Value theory, the paper provides an explanation in the form of a process of how doctoral destinations are selected based on it and adds to the scholarly literature on the subject of South-South movement of students, doctoral education across the borders, and making decisions about the destination.